The 2022-2023 Russia-Ukraine War and Cyberspace Threats - Lika Lagvilava (International Society of Philosophy and Cosmology, 2023)
In the 21st century, following the process of globalization, the importance of the Internet is increasing, continuous remote communication is carried out, electronic purchases are made, payments are made in electronic form, and official and unofficial correspondence is exchanged between actors and institutions both within the country and abroad. Remote services are developing both in the private and public sectors. Therefore, Internet users, service recipients, legal entities, public agencies, and, in general, any citizen who communicates electronically in public space using remote services are under threats from cyberspace. However, it should also be noted that with the rise in popularity of the Internet, a new era of technological challenges are making the threats from cyberspace become apparent. Addressing these threats requires a comprehensive and multi-layered approach, including robust cybersecurity practices, regular updates and patching of software, user education and awareness, cooperation between governments and private sectors, and the development of international norms and agreements to prevent and respond to cyber threats. The technological progress of the world is so comprehensive that we face its consequences in all fields, including wars between states. No one is surprised anymore that today wars are taking place simultaneously in two dimensions - physical and digital worlds. Such is the daily life of two-sided military battalions of the twenty-first century, which became the focus of people's attention after the start of the Russia-Ukraine war. The presented article discusses cyber attacks carried out by Russia on the territory of Ukraine as a result of the Russian-Ukrainian war. The aim of the paper is to show how important the issue of cyber security is in modern wars and what policies states should implement to neutralize threats from cyberspace.